2019
DOI: 10.1080/2162402x.2019.1576490
|View full text |Cite
|
Sign up to set email alerts
|

T cell repertoire to citrullinated self-peptides in healthy humans is not confined to the HLA-DR SE alleles; Targeting of citrullinated self-peptides presented by HLA-DP4 for tumour therapy

Abstract: Post-translational modifications are induced in stressed cells which cause them to be recognised by the system. One such modification is citrullination where the positive charged arginine is modified to a neutral citrulline. We demonstrate most healthy donors show an oligoclonal CD4 response in vitro to at least one citrullinated vimentin or enolase peptide. Unlike rheumatoid arthritis patients, these T cell responses were not restricted by HLA-DRB1 shared epitope (SE) alleles, suggesting they could be present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 37 publications
5
39
0
Order By: Relevance
“…In contrast, immunization with Aldo238-256 Hcit peptide showed no significant survival advantage despite inducing an immune response and also providing evidence that CpG/MPLA adjuvant has no antitumor effect in this model which is consistent with previous data. 5 These results suggest that Aldo74-93 and Aldo140-157 peptides are naturally homocitrullinated and presented on MHC-II, whereas Aldo238-256 is either not naturally homocitrullinated or not presented in vivo.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…In contrast, immunization with Aldo238-256 Hcit peptide showed no significant survival advantage despite inducing an immune response and also providing evidence that CpG/MPLA adjuvant has no antitumor effect in this model which is consistent with previous data. 5 These results suggest that Aldo74-93 and Aldo140-157 peptides are naturally homocitrullinated and presented on MHC-II, whereas Aldo238-256 is either not naturally homocitrullinated or not presented in vivo.…”
Section: Resultsmentioning
confidence: 83%
“…Previous studies have shown that citrullinated peptides are presented on HLA-DP4, an HLA allele that is frequently expressed in the Caucasian population. 5 We aimed to determine if homocitrullinated peptides could be presented on HLA-DP4 molecules on the cell surface. IEDB algorithm was used to predict potential peptides from aldolase, Bip, Cyk8 and enolase that have a strong or moderate predicted binding affinity to HLA-DP4 (DPA1*01/DPB1*04:01) and contain lysine residues in the predicted core binding regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its ubiquitous expression, ENO1 is often degraded during autophagy; previous studies have also shown that ENO1 can be citrullinated ( 65 , 83 ). We have shown that these citrullinated peptides are recognized and presented to CD4+ T cells by both MHC class II HLA-DR4 and HLA-DP4 molecules ( 49 , 84 , 85 ). HLA transgenic mice vaccinated with citrullinated vimentin and α-enolase peptides linked to an adjuvant (Modi-1 vaccine) can stimulate CD4+ T cells ( 49 , 64 , 86 ) and generate potent anti-tumor responses resulting in tumor regression and eradication with no associated toxicity ( 49 , 87 ).…”
Section: Target Antigensmentioning
confidence: 99%
“…The high diagnostic sensitivity and specificity of anti-MCV as well as its predictive value for erosive disease provide indirect evidence for citrullinated vimentin as an important molecule for driving the pathological immune response in RA. These earlier reports of RA demonstrate that at least one citrullinated peptide, but not its arginine-containing counterpart, can drive a T-cell response in the context of the HLA-DRB1*0401 molecule [ 47 ]. However, unlike citrullinated fibrinogen, citrullinated vimentin has yet to be demonstrated to be arthritogenic in an in vivo animal model.…”
Section: Citrullinated Vimentin In Ramentioning
confidence: 99%